DESKRIPTIF KEMAMPUAN BERPIKIR KRITIS SISWA DALAM PEMECAHAN MASALAH MATERI PENGUKURAN DI KELAS IV - Ainiya Tamira; Bistari Bistari; Hery Kresnadi (Universitas Tanjungpura, 2020)
describe the students’ ability in critical thinking in problem solving of measurement subject in grade IV of elementary school of Muhammadiyah 2 Pontianak. Facione’s opinion was used as an indicator, which consist of, identify the problem, determine relevant information, enumerate options, assess the situation and make a preliminary decision, scrutinize the process and self-correct. The type of this research is qualitative, with case study methode. Data sources in this research are the grade IV student of elementary school of Muhammadiyah 2 Pontianak. The data that has been collected are from the students’ ability in critical thinking and interview. The result of this research shows that the lack of grade IV students’ ability in critical thinking. In identify the problem indicator, shows that the students tend to give a deficient answers, in determine relevant information indicator, shows that the students tend to give a deficient answers, in enumerate options indicator, shows that the students tend to give a deficient answers, in assess the situation and make a preliminary decision indicator, shows that the students tend to give a deficient answers, and in scrutinize the process and self-correct, shows that the students tend to give a correct answers.Keyword: Ability in Critical Thinking, Measurement Subject, Problem Solving,